Dual Ligand Chelates: Preparation and Spectroscopic Characterization - Larial, Fatima Y.; Alakib, Mohammed; Salem, Halima F.; El-ajaily, Marei M.; Al-Noor, Taghreed H. (AlQalam Journal of Medical and Applied Sciences, 2025)
Here, we synthesized three new blended ligand complexes of chromium (III), iron (III), and lanthanum (III) ions with a Schiff base made from the condensation of [o-aminophenol and 2-hydroxyacetophenone in the presence of concentrated sulphoric acid (HL1)] as a primary ligand and o-nitroaniline (L2) as a secondary. The Schiff base and its dual ligand chelate were characterized using several spectroscopic studies, IR, 1HNMR, electronic and mass spectra, in addition to elemental analyses, molar conductivity measurements, and magnetic moments. The spectroscopic and analytical outcomes confirmed the formation of the chelates in a 1:1:1(L1: M: L2) ratio. Similarly, an octahedral structure became counseled for all chelates.